Overview and Recommendations on Worrying SARS-CoV-2 Virus Variants (VOC) - K. Shneine, Jawad; M. Ahmad, Shayma (Al-Nahrain Journal of Science, 2022)
This work introduces briefly an overview and recommendations on worrying SARS-CoV-2 Virus variants, that can be interpreted as the most spread ones till now. They are: Lineage B.1.1.7, Lineage B.1.351, and Lineage P.1. It is also displayed their observations and development in definite locations in Germany as an exemplary version.